New Learners’ Experiences in Using e-Learning Technology in the Open University Malaysia - Latifah Abdol Latif; Ramli Bahroom; Ng, Man San (ASEAN Journal of Open and Distance Learning, 2012)
As an attempt to reduce the high attrition rate among its new students, Open University Malaysia (OUM) has been encouraging learners to use e-learning technology and digital learning materials for their studies and interaction with the university’s academic staff. This paper reports the findings of a study that examined new learners’ experiences at OUM in using e-learning technology and digital learning materials. The study was based on 438 usable questionnaires completed by a random sample of new learners. The constructs used include perceived usefulness, perceived ease of use, computer self-efficacy and anxiety. The study found that new learners at OUM were generally receptive towards e-learning technology and digital learning materials. Usage of mobile devices for downloading study materials such as HTML modules, i-Lectures and i-Radio learning segments ranged from high for laptops and mobile phones to moderate for MP3 and MP4 players to low for tablet computers. There is no significant difference in elearning technology usage between older and younger cohorts. An interesting finding of the study was that perceived usefulness was the only significant factor influencing the use of technology while other factors including attitude were not. Finally, the study found that there are significant barriers to e-learning usage, principal among them are technology and academic support, time, and accessibility. [ABSTRACT BY AUTHORS]